2021
DOI: 10.31186/jspi.id.16.2.164-170
|View full text |Cite
|
Sign up to set email alerts
|

Penambahan Nukleotida pada Ransum Broiler yang Dipelihara pada Suhu Lingkungan Berbeda terhadap Performa Organ Imunitas

Abstract: This study was aimed to know the effects of dietary nucleotide on the immune organs performance of broiler chickens raised under different environmental conditions. The material used was unsexed 165 birds broiler chickens 15 days old with an average body weight of 462.20±9 g (CV 3.95%), and nucleotide supplemen. The experiment was completely randomized design with factorial patern 3×3 and 5 repeats. The first factor is three different levels of dietary nucleotide T0=0g/kg, T1=0.5g/kg and T2=1g/kg of feed and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
1
Order By: Relevance
“…The index of bursa fabricius (BFI) and lien index (LI) of broiler chickens in this study were 2.26-2.39% and 0.11±-0.15% (Table 3). BFI and LI in this study were higher than those of Hakim et al (2021), reporting that BFI and LI in broiler chickens supplemented with nucleotide were only 0.044-0.047% and 0.112-0.146%, respectively. The result of the analysis of variance showed that the supplementation of nucleotide and turmeric extract and different types of floors did not significantly affect (P>0,05) LI, but this combination significantly affected (P<0,05) the BFI of broiler chickens.…”
Section: Physiological Statuscontrasting
confidence: 59%
“…The index of bursa fabricius (BFI) and lien index (LI) of broiler chickens in this study were 2.26-2.39% and 0.11±-0.15% (Table 3). BFI and LI in this study were higher than those of Hakim et al (2021), reporting that BFI and LI in broiler chickens supplemented with nucleotide were only 0.044-0.047% and 0.112-0.146%, respectively. The result of the analysis of variance showed that the supplementation of nucleotide and turmeric extract and different types of floors did not significantly affect (P>0,05) LI, but this combination significantly affected (P<0,05) the BFI of broiler chickens.…”
Section: Physiological Statuscontrasting
confidence: 59%
“…Data (Table 1 and Figure 4) shows relative weight of bursa fabricius T2 better than T1 and T3 that have decreased. Hakim et al [51] stated that chickens that are raised under stress conditions, such as the increase of room temperature and high density of the closed house, will reduce the relative weight of bursa fabricius. The same statement conveyed by Pamok et al [52] that in general, bursa fabricius in chicken that has heat stress may become an atrophy and reduce the number of lymphocytes.…”
Section: Weight Of Bursa Fabriciusmentioning
confidence: 99%
“…This is because with a very fluctuating cage temperature ranging from 26 to 33 0 C, the cage temperature conditions cause chickens to experience stress. This condition is not be able to meet the adequacy of nucleotide in their body for broiler chickens (Hakim et al, 2021). In addition, it will cause damage to erythrocytes, this is because the chicken in heat stress conditions will trigger the formation of free radicals or reactive oxygen compounds.…”
Section: Profile Of Bloodsmentioning
confidence: 99%